Assessing the Performance of Nano Lubricant on Zinc Aluminium Alloy - Murugaveni, S Parimala; Thyla, P R (Defence Science Journal, 2019)
In the field of tribology, Zinc Aluminium (ZA) alloys have been widely investigated for their superior wear characteristics. They were found to be suitable alternatives for bearing bronzes for the operating conditions of high mechanical load and moderate sliding speeds. Addition of nano-particles in the lubricating oil (base oil) to enhance the characteristics of the base oil is known as nano lubrication. In this study, sliding wear behaviour of ZA27 was investigated under dry, base oil and nano oil lubrication conditions, by varying load, sliding distance and sliding speed. With the base oil as SAE 40, nano graphite was added in two step method which was further used to identify the lubrication regime under different lubrication conditions. From the limited study of single melt samples, the results appear that the wear behaviour of ZA27 alloy improved under nano lubrication conditions with reduction in operating temperature. It could be observed from SEM images that the presence of nano-particles reduced scarring and wear, leading to enhancement in the tribological performance of ZA27 alloy.